A meridional dipole in premonsoon Bay of Bengal tropical cyclone activity induced by ENSO. Issue 12 (30th June 2016) - Balaguru, Karthik; Leung, L. Ruby; Lu, Jian; Foltz, Gregory R.
Abstract: Analysis of Bay of Bengal tropical cyclone (TC) track data for the months of May–June during 1979–2014 reveals a meridional dipole in TC intensification: TC intensification rates increased significantly in the northern region and decreased in the southern region. The dipole is consistent with changes in the large‐scale TC environment estimated using the Genesis Potential Index (GPI) for the same period. While an increase in lower troposphere cyclonic vorticity and midtroposphere humidity in the northern Bay of Bengal made the environment more favorable for TC intensification, enhanced vertical wind shear in the southern Bay of Bengal tended to reduce TC development. These environmental changes were associated with a strengthening of the monsoon circulation for the months of May–June, driven by a La Niña‐like shift in tropical Pacific SSTs and associated tropical wave dynamics. Finally, analysis of a suite of climate models from the Coupled Model Intercomparison Project Phase 5 archive shows that most models correctly reproduce the link between ENSO and premonsoon Bay of Bengal TC activity at interannual timescales, demonstrating the robustness of our main conclusions. Key Points: Changes in TC intensification during the premonsoon months of May‐June in the Bay of Bengal resemble a meridional dipole These changes in TC activity are consistent with those in the environment that suggest a strengthening of May‐June monsoon circulation Decadal changes in ENSO impacted premonsoon Bay of Bengal TC activity through remote teleconnection mechanisms